Kajian Kualitas Jalur Pejalan Kaki Pasca Revitalisasi di Koridor Jalan Jenderal Sudirman DKI Jakarta - Dwisadana, Martinus Aditya; Widjajanti, Retno (Teknik PWK (Perencanaan Wilayah Kota), 2024)
Pedestrian ways is one of the eight elements of urban design, whose existence becomes an urgency in urban areas. Not only its existence, but its quality must be maintained. Jenderal Sudirman is one of the main roads located in the administrative areas of Central Jakarta, to be precise in the Sudirman Central Business District, where most of Jakarta’s financial and business activity located. Jenderal Sudirman pedestrian ways has been through revitalization from 2018 until 2020, which aims to improve the physical quality of pedestrian ways and public interest in walking. Although the revitalization has been carried out, there are still several problems related to pedestrian safety and convenience. According to one of DKI Jakarta’s visions in 2022, namely towards more walkable city through creating a complete, safe, and comfortable pedestrian ways, that also supports the use of public transportation, as well as creating sustainable city, the attention of most basic human movement in the form of walking needs to be focused. This improvement needs to be supported through a study of the planning and provision of pedestrian ways. Therefore this study will examine the quality of the pedestrian ways based on the physical condition of the pedestrian ways and pedestrian perception. The results of the two analyzes will be assessed using the Pedestrian Environmental Quality Index (PEQI) approach, so that both results can be compared and can complement each other. The PEQI assessment will produce outputs in the form of quality classification and description of post revitalization Jenderal Sudirman pedestrian ways, as well as recommendations in the form of spatial planning based on several deficiency in the results of the assessment.